Detection and molecular characterisation of Grapevine Syrah virus-1 isolates from Central Europe - Glasa, Miroslav; Predajňa, Lukáš; Šoltys, Katarína; Sabanadzovic, Sead; Olmos, Antonio (Virus genes, 2015)
Grapevine Syrah virus-1 (GSyV-1) was identified by small-RNA deep sequencing in Slovak grapevine co-infected by several other viruses. The RT-PCR assays developed in this work substantially improved the virus detection and allowed the identification of GSyV-1 in tested grapevine samples from Slovakia and the Czech Republic at an unexpectedly high rate (ca. 30 %). Subsequently, complete genome sequences of 3 GSyV-1 isolates (2 Slovak and 1 Czech) were determined by Sanger sequencing, showing a typical marafivirus genome organization. Analyses of complete genome sequences showed a higher intra-group diversity among these 3 central European GSyV-1 isolates (differences reaching 7.1 % at the nucleotide level) in comparison to 3 previously characterized North American isolates (only 1.2 % intra-group divergence). A substantially higher divergence among central European isolates and their clustering into two major phylogenetic groups was further confirmed by the partial genome analysis of additional 26 isolates. The CP-centered study did not support the geography-based clustering among central European and American isolates. Nevertheless, the sequence data of the highly variable 5'-proximal portion of the genome obtained for few additional isolates from Slovakia and Czech Republic showed the presence of both, "European-" and "north American-like", GSyV-1 isolates in the analyzed grapevine samples.
Keywords: RNA, Viral; RNA virová; Sequence Homology, Nucleic Acid; Cluster Analysis; Slovakia; Vitis; Slovenská republika; genetická variace; Genome, Viral; fylogeneze; Česká republika; Sequence Analysis, DNA; Phylogeny; sekvenční analýza DNA; Tymoviridae; molekulární sekvence - údaje; shluková analýza; sekvenční homologie nukleových kyselin; Gene Order; Czech Republic; Molecular Sequence Data; genom virový; Genetic Variation; pořadí genů